Multigenic delineation of lower jaw deformity in triploid Atlantic salmon (Salmo salar L.) - Gianluca Amoroso; Ventura, T; Cobcroft, JM; Mark Adams; Elizur, A; Christopher Carter (2016)
Lower jaw deformity (LJD) is a skeletal anomaly affecting farmed triploid Atlantic salmon ( Salmo salar L.) which leads to considerable economic losses for industry and has animal welfare implications. The present study employed transcriptome analysis in parallel with real-time qPCR techniques to characterise for the first time the LJD condition in triploid Atlantic salmon juveniles using two independent sample sets: experimentally-sourced salmon (60 g) and commercially produced salmon (100 g). A total of eleven genes, some detected/identified through the transcriptome analysis ( fbn2 , gal and gphb5 ) and others previously determined to be related to skeletal physiology (alp , bmp4 , col1a1 , col2a1 , fgf23 , igf1 , mmp13 , ocn ), were tested in the two independent sample sets. Gphb5 , a recently discovered hormone, was significantly ( P < 0.05) down-regulated in LJD affected fish in both sample sets, suggesting a possible hormonal involvement. In-situ hybridization detected gphb5 expression in oral epithelium, teeth and skin of the lower jaw. Col2a1 showed the same consistent significant ( P < 0.05) down-regulation in LJD suggesting a possible cartilaginous impairment as a distinctive feature of the condition. Significant ( P < 0.05) differential expression of other genes found in either one or the other sample set highlighted the possible effect of stage of development or condition progression on transcription and showed that anomalous bone development, likely driven by cartilage impairment, is more evident at larger fish sizes. The present study improved our understanding of LJD suggesting that a cartilage impairment likely underlies the condition and col2a1 may be a marker. In addition, the involvement of gphb5 urges further investigation of a hormonal role in LJD and skeletal physiology in general.